Asymetrix Currency Turbulence with US Dollar/Japanese Yen Carry Trade: Insights into Central Bank Interventions and Exchange-Rate Dynamics - Masaaki Yoshimori (Financial Markets, Institutions and Risks)
This study investigates the time-varying effectiveness of central bank interventions in the USDJPY exchange rate market, focusing on their asymmetric impacts under varying market conditions. Quantile regression is employed to analyze intervention outcomes across various segments of the exchange rate distribution, with particular focus on extreme scenarios represented by the 90th quantile. The results reveal that interventions are most effective during periods of lower exchange rate levels, as indicated by the significant negative coefficients at the 10th quantile. However, their influence diminishes at higher quantiles, where extreme market pressures dominate. Key structural factors, such as interest rate differentials and global volatility (proxied by the VIX index), play a dominant role in driving exchange rate dynamics. In particular, the interest rate differential between US and Japanese 10-year bond yields strongly influences the exchange rate, while market volatility reinforces the yen’s status as a safe-haven currency. Although the model’s explanatory power is limited (low pseudo-R² values), the QR analysis highlights the conditional nature of intervention effectiveness. These findings suggest that while interventions can provide short-term stabilization, particularly when the yen faces downward pressure, their overall impact is modest compared to the influence of structural economic factors.The study concludes that while direct central bank interventions are limited in standalone effectiveness, they play a crucial complementary role during market turbulence by tempering extreme fluctuations caused by speculative pressures or external shocks. However, interventions alone cannot mitigate exchange rate volatility under extreme conditions. A broader framework integrating interventions with monetary policy and addressing economic drivers like interest rate differentials and global sentiment is essential for effective exchange rate management.